1998
DOI: 10.1093/sf/77.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Inciting Sociological Thought by Studying the Deadhead Community: Engaging Publics in Dialogue

Abstract: Abstract:We need to pay more attention to the process of being sociologists and less attention to rates of productivity. To support this statement, I present a case study of the processes in which I have been involved while studying Deadheads, fans of the former rock band, the Grateful Dead. To avoid negative sanctioning, I proceeded slowly with this research and therefore had time to engage students, the media, and Deadheads in sociological dialogue. As a result, my teaching, ability to communicate sociologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Social movement scholars should heed Adams (1998) call to study popular culture and its increasing effects in society. The peace movement provides examples of popular musicians such as Crosby, Stills, Nash, and Young in the 1960s to the band Green Day, more recently, giving their time to help the cause (Garofalo 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Social movement scholars should heed Adams (1998) call to study popular culture and its increasing effects in society. The peace movement provides examples of popular musicians such as Crosby, Stills, Nash, and Young in the 1960s to the band Green Day, more recently, giving their time to help the cause (Garofalo 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Further, research in festivals remains important as behavior and customs found at festivals can be considered exemplary of ceremony and ritual in modern society (Shrum and Kilburn ). There are relatively few sociological studies of festivals or the Burning Man festival itself (but see Adams ; Chen , , , ; Doherty ; Gotham ; Sherry and Kozinets ), however, Burning Man and associated regional burn festivals may provide insight for scholars interested in lifestyle‐based politics because of their relative longevity, counter‐cultural nature, and shared meaning and ideology (Chen ).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Perhaps even more astounding than their prolific concert performances is the dedication that their fans (known as "deadheads") had to their music [13,1,17,16]. The typical deadhead was not a passive consumer of recorded studio albums, but an active concert goer that traveled with the band from concert to concert, city to city, and country to country.…”
Section: Introductionmentioning
confidence: 99%